An Electrochemical Quartz Crystal Microbalance Study on Electrodeposition of Aluminum and Aluminum-Manganese Alloys. Issue 8 (10th June 2017) - Ispas, A.; Wolff, E.; Bund, A.
Abstract : The electrodeposition process of aluminum and aluminum-manganese alloys was studied in situ, by using an electrochemical quartz crystal microbalance, EQCM, with damping monitoring, in AlCl3 based ionic liquids. Cyclic voltammetry, potentiostatic and galvanostatic deposition were performed at different temperatures, from 25°C up to 100°C. The morphology of the deposits was investigated by SEM and AFM, and their composition by EDX. The stoichiometry of the alloys was calculated from the EQCM data, based on Sauerbrey's equation. We could show that for thin films electrodeposited on gold electrodes, one can tune their morphology, and in the case of the alloys, also their composition, by modifying the deposition current or potential, as well as by modifying the temperature of the electrolyte. The morphology of the deposits changed gradually with increasing the amount of Mn in the electrolyte from a polyhedral like structure for Al films to round granules for the AlMn alloys. The mechanism for electrodeposition and dissolution of Al and AlMn alloys were analyzed and discussed based on the EQCM data.